دور التكنولوجيا المالية في تطوير الخدمات المصرفية لتحقيق الشمول المالي في الجزائر - قدوري, طارق; زغدي, باديس (جامعة الوادي - University of Eloued, 2022)
هدفت هذه الورقة البحثية إلى معرفة أنماط الخدمات المصرفية الحديثة الناتجة عن التطور التكنولوجي وارتباطه بالقطاع المالي، ومدى تطبيق ذلك في القطاع المصرفي والمالي ومساهمته في مسعى تحقيق الشمول المالي في الجزائر. وفق منهج وصفي مقارن، وقد توصلت الدراسة إلى أن القطاع المصرفي والمالي في الجزائر يشهد تطورا ملحوظا رغم ضعف سيرورة تحسن مؤشرات الدخول إلى الشمول المالي المستهدف The purpose of the research paper to know the methods of modern banking services resulting from technological development and its connection to the financial sector, and the extent of its application in the banking and financial sector and its contribution to the endeavor to achieve financial inclusion in Algeria. According to a comparative descriptive approach, the study concluded that the banking and financial sector in Algeria is witnessing a remarkable development despite the weak process of improving entry indicators to the targeted financial inclusion
The role of financial technology in developing banking services to achieve financial inclusion in Algeria.
مقال
Keywords: الشمول المالي ; التكنولوجيا المالية ; القطاع المصرفي ; الجزائر; Financial Inclusion ; Fintech ; The banking sector ; Algeria